Does better environmental performance lead to improved bottom lines? A theoretical framework - Hamoudah, Manal; Sulaiman, Maliah; Mohd Alwi, Norhayati; Abideen, Adewale Abideen (Technische, Universitat Dresden, 2013)
Over 40 years of study, researchers have not been able to identify a clear cut relationship between a company’s environmental performance (FP) and its financial performance (EP). For that reason, this paper provides the theoretical framework on the relationship between the two. This framework considers a dual perspective from traditional economic research and strategic management field in an attempt to justify the paradoxical results. Specifically the study posits whether companies do well financially under shareholder theory or do good environmentally under resource-based-view (RBV). Further, in attempt to address the methodological shortcomings, especially as it relates to the lack of a robust measure of EP, the current paper proposes four indicators from two broad dimensions. The indicators based on strategic dimension include: top management commitment (TMC) and EMS-ISO14001 certifications, while the operational dimension indicators are both environmental strategy (ES) and programs to reduce environmental impact (PREI).